True Love In Gary Winick's Letter To Julie Movie (2010): An Existentialist Approach - Suyana, Yuly (2012)
This study is about secret of the truth in Letter to Juliet movie (2010). This objective of the study is to apply the Existentialist approach to analyze true love in Letter to Juliet movie (2010). The writer uses Sartre's major point of Existentialism to answer the problem of the study. The study is descriptive qualitative research whose data are taken from script in Letter to Juliet. The technique of analyzing data is descriptive. The study comes to the following conclusions. First, based on the structural analysis of each elements, it shows that the character and characterization, plot, setting, point of view, theme, casting, mise-en-scene, cinematography, sound, and editing are related to each other and form the unity. Second, based on the existentialist analysis, humans have different existences, their existences are based on different being, choice, and act. Human has a freedom to choose and then responsible for his existence. The responsibility will appear in an anxiety. Gary Winick shows the struggle and the meaning of true love. He believes that true love never look at the age, and social background. Love has a big power and something which is important in human life.